+0  
 
0
42
1
avatar

Find the sum of all x that satisfy the equation -9x/(x^2 - 1) = 2x/(x + 1) - 6/(x - 1) + 5/(x + 1).

 Apr 11, 2022
 #1
avatar+122390 
+1

Note that  (x^2 - 1)  = (x + 1) (x -1)

 

Multiplying through by the factorization we get that

 

-9x  = 2x(x -1) - 6(x + 1) + 5(x -1)          simplify

 

-9x  = 2x^2 -2x -6x -6 + 5x - 5

 

2x^2  + 6x  - 11 = 0

 

Using the Quadratic Formula  and simplifying

 

x  =  [   -3 + sqrt (31) ]  /2   

And

x = [ -3 -sqrt (31)  ] /  2

 

 

cool cool cool  

 Apr 11, 2022

21 Online Users

avatar
avatar
avatar